DREAM Project: Decreasing REcurrent pain and Anxiety in Medical procedures on a pediatric population - Le May, Sylvie; Paquin, David; Bouchard, Stéphane; Fortin, Jean-Simon; Khadra, Christelle (International Journal of Virtual Reality, 2016)
The DREAM project is a joint venture between the medical world, university professors and developers with one goal in mind: create an efficient distraction tool to reduce pain and anxiety in children receiving medical treatments. Growing evidence in the medical literature suggests that virtual reality is a very potent and effective way of creating distraction. In turn, distraction has been shown to reduce pain and anxiety in children who are receiving painful medical procedures. The pediatric population offers quite a challenge when it comes to pain control, especially the pain caused by medical procedure. Anxiety and anticipation greatly modulates pain perception and can often jeopardize a treatment if a child's collaboration cannot be obtained. With those premises in mind, our team is trying to create an efficient virtual reality game for distracting kids from their pain. The DREAM game has been tailored for the very specific needs and characteristics of our target population. The experience is optimized for the oculus rift and the controls have been simplified to work in various medical settings with minimal preparation time. Our main concern was to create a game that delivers a potent distractive effect while inciting almost no side effects or cyber sickness. The DREAM project is currently being tested on children with burn injuries. The objective of this paper is to present the methodology used to validate our hypotheses.